A Comparative Study of the Strong Believer and the Weak Believer in the Light of Islamic Teachings - Dr. Nisar Mehmood; Ms Salma Bibi (Journal of Religion and Society, 2024)
This paper with the title A Comparative Study of the Strong Believer and the Weak Believer in the Light of Islamic Teachings seeks to examine the qualitative distinctions of a strong believer (Mu Min Qawi) and a weak believer (Mu Min Da eef) as defined in the Quran and Sunnah. Based on the prophetic saying, which goes, The strong believer is better and more beloved to Allah than the weak believer (Sahih Muslim), the study explores the complex nature of faith (iman) that is not only belief, but also moral power, practical faith, emotional stability and social accountability. In the study, dimensions are addressed including firmness in belief, consistency in worship, patience through trials, ethical conduct and impact to the society. It bases its mainline sources on the works of such scholars as Imam Ibn Taymiyyah, Imam Ghazali, Imam Nawawi, and Imam Ibn Qayyim to develop theological and practical definitions of strong and weak faith. The study makes an outright comparison between the two types of believers on the basis of psychological stability, how they face hardships, how they make decisions and how they respond to divine challenges. At the applied level, the true believer is regarded as more regular in religious practices like praying as well as fasting and recitation of the Quran. They are also more confident in Allah, have better morals and are involved in correction and dawah in society. The weak believer, on the contrary, is prone to collapse during hard times, is lax in performing his worships, and is weak and inconsistent. The research also highlights the statement that weak believers are not branded in hell but are helped to become strong by seeking the knowledge of the religion, righteous companionship, consistency in prayers, and self-ethical enhancement. This comparative discourse is neither an abstract discussion nor a focus on reformation to oneself and society. It promotes Muslim self-reflection as well as effort to become a good believer capable of serving the society and determined to avoid difficulties. The work ends with the practical advice and supplications on how to achieve the spiritual power and nearness to God. The end product of this research therefore is to motivate believers to aim at excellence in faith, deed and character thereby drawing near to the perfect example of a beloved servant in the eyes of Allah. Keywords: Strong Believerm, Weak Believer, Iman (Faith), Islamic Teachings, Qur’an and Hadith, Spiritual Strength, Personal Development